A generalized Omori–Yau maximum principle in Finsler geometry. (November 2015) - Yin, Song-Ting; He, Qun
Abstract: We obtain some new Laplacian comparison theorems on Finsler manifolds with the (weighted) Ricci curvature bounded from above (resp. below) by a smooth function. Then, under some new sufficient conditions, we generalize the Omori–Yau type maximum principle in the Finsler setting.